The Potential of Food Waste-Derived Organic Fertilizer Produced Using Biopore Technology on the Growth of Spinach (Amaranthus hybridus) - Aulia Putri Ramadhani; I Nengah Kundera; Manap Trianto; Lilies Tangge; Yulia Windarsih; Amalia Buntu (Biology, Medicine, & Natural Product Chemistry, 2026)
Food-wasting behavior contributes significantly to the increasing volume of household organic waste, which has the potential to pollute the environment if not managed properly. This study aimed to describe the potential of food waste processed using the biopore technique as an organic fertilizer for the growth of spinach (Amaranthus hybridus) and to determine the optimal application concentration that promotes the best plant growth. This study employed an experimental method using a Completely Randomized Design (CRD). Five concentrations of biopore organic fertilizer were tested with four replications: P0 (control/no fertilizer), P1 (25 g), P2 (50 g), P3 (100 g), and P4 (150 g). The observed parameters included plant height (cm), number of leaves, and leaf area (cm2), which were measured periodically for four weeks after planting (WAP). The collected data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that the application of biopore organic fertilizer derived from food waste had a significant effect on all growth parameters evaluated. Based on the post hoc analysis, treatment P4 (150 g/L concentration, equivalent to 15%) consistently produced the best growth performance. At the end of the observation period (4 WAP), P4 resulted in an average plant height of 13.23 cm, an average of 8 leaves per plant, and a leaf area of 6.10 cm2. These values were significantly higher than those of the control group (P0) and the other lower-concentration treatments. In conclusion, food waste decomposed through biopore holes has considerable potential to be utilized as an agronomically valuable organic fertilizer. A concentration of 15% (P4) is recommended as the most effective formulation for sustainably promoting the growth of Amaranthus hybridus L. plants.